1995
DOI: 10.1097/00132586-199504000-00036
|View full text |Cite
|
Sign up to set email alerts
|

Transdermal Administration of Morphine to Healthy Subjects

Abstract: 1 Twelve healthy subjects received 10 mg morphine HCI delivered transdermally from an occlusive reservoir applied to a small area of skin, painlessly de-epithelialised by vacuum suction. On a separate occasion, 10 mg morphine HCI was given as an i.v. infusion over 20 min. 2 Venous blood samples were collected serially for 72 h and assayed for morphine, morphine-3-glucuronide (M3G) and morphine-6-glucuronide (M6G) by h.p.l.c. Pupil size, salivation, and central nervous effects ( nausea, fatigue, headache, feeli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 4 publications
0
10
0
Order By: Relevance
“…This technique was developed by a group in Sweden in the 1990s and is now available as the commercial product Cellpatch which is used to deliver morphine in postoperative pain. 117 They also reported the application of the antidiuretic peptide 1-deamino-8-D-arginine vasopressin with close to 100% bioavailability in healthy human subjects 118 with recovery of the skin spot to normal after 6 weeks. No further research into this technique has been undertaken in the past 10 years or by other groups so it is unlikely that this technique will progress further for peptide delivery.…”
Section: Suction Blister Ablationmentioning
confidence: 99%
“…This technique was developed by a group in Sweden in the 1990s and is now available as the commercial product Cellpatch which is used to deliver morphine in postoperative pain. 117 They also reported the application of the antidiuretic peptide 1-deamino-8-D-arginine vasopressin with close to 100% bioavailability in healthy human subjects 118 with recovery of the skin spot to normal after 6 weeks. No further research into this technique has been undertaken in the past 10 years or by other groups so it is unlikely that this technique will progress further for peptide delivery.…”
Section: Suction Blister Ablationmentioning
confidence: 99%
“…Unlike fentanyl, the transdermal absorption of morphine has not been widely published. An early report by Westerling et al [29] . suggested that the absolute bioavailability of transdermal morphine, across de‐epithelianised skin was 75%.…”
Section: Systemic Absorption From Topically Applied Opioidsmentioning
confidence: 99%
“…Dryness of the mouth is a side effect of morphine (28,29) that was reported to be highly associated with morphine therapy in chronic pain patients (30). Following different routes of morphine administration to healthy volunteers, a significant reduction of saliva production was registered (9)(10)(11). Also, hydromorphone, given as an intravenous infusion over 20 mins, significantly reduced saliva production (12), which in the present analysis was shown to be well related to the estimated concentration of the opioid in a hypothetical effect compartment.…”
Section: Discussionmentioning
confidence: 99%
“…The analgesic effect of opioids is difficult to quantify and compare between individual subjects, whereas in healthy subjects, experimental pain lacks the emotional components of clinical pain. Unlike analgesia, side effects of opioids, such as miosis and decrease of saliva production, can be measured accurately (9)(10)(11)(12). The E max model (13,14) was applied after administration of morphine to healthy subjects (9,11), where these nonanalgesic effects were shown to be related to estimated effect compartment concentrations.…”
mentioning
confidence: 99%
See 1 more Smart Citation